2006
DOI: 10.1007/s10974-006-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Striated Muscle Degeneration by Serotonin in C. elegans

Abstract: Prevention of muscle fiber degeneration is a key issue in the treatment of muscular dystrophies such as Duchenne Muscular Dystrophy (DMD). It is widely postulated that existing pharmaceutical compounds might potentially be beneficial to DMD patients, but tools to identify them are lacking. Here, by using a Caenorhabditis elegans model of dystrophin-dependent muscular dystrophy, we show that the neurohormone serotonin and some of its agonists are potent suppressors of muscle degeneration. Inhibitors of serotoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
2
28
0
2
Order By: Relevance
“…DMD is mostly described by a dynamic loss of solid mass and capacity happening in guys because of transformations in the DYSTROPHIN quality situated on the X chromosome, which usually prompts to loss of motion and demise by the age of 30. DYSTROPHIN is both solid and neuronal, being required for cerebrum design and neurotransmission, to such an extent that DMD patients show neurodegeneration related with engine shortfalls and diminished subjective exhibitions (normal IQ is 85 in DMD young men) [174][175][176][177]. DYSTROPHIN is monitored in C. elegans, however its loss-of-capacity in the worm brings about hypercontractility because of debilitated cholinergic movement and does not influence muscle cells [178,179].…”
Section: Pathwaysmentioning
confidence: 99%
“…DMD is mostly described by a dynamic loss of solid mass and capacity happening in guys because of transformations in the DYSTROPHIN quality situated on the X chromosome, which usually prompts to loss of motion and demise by the age of 30. DYSTROPHIN is both solid and neuronal, being required for cerebrum design and neurotransmission, to such an extent that DMD patients show neurodegeneration related with engine shortfalls and diminished subjective exhibitions (normal IQ is 85 in DMD young men) [174][175][176][177]. DYSTROPHIN is monitored in C. elegans, however its loss-of-capacity in the worm brings about hypercontractility because of debilitated cholinergic movement and does not influence muscle cells [178,179].…”
Section: Pathwaysmentioning
confidence: 99%
“…Despite large differences in anatomical and biochemical properties between mammals and invertebrates, it has been shown that there are enough similarities and correspondences to use C. elegans as a model host for research of a variety of diseases and medications. Many C. elegans mutant strains can mimic human diseases such Alzheimer's disease, Duchenne muscular dystrophy, diabetes, and cancer [7680] . A very important factor in utilizing C. elegans in antimicrobial discovery is that there are similarities between microbial pathogenesis in mammals and C. elegans ; therefore, compounds with antimicrobial property detected in C. elegans are highly likely to be compounds which can be used in humans.…”
Section: C Elegans In Drug Discoverymentioning
confidence: 99%
“…This first pilot screen served as a proof-of-principle study suggesting that drugs used to treat patients with dystrophin-associated disease can be highlighted in a C. elegans model. A second slightly larger screen of bioactive molecules highlighted serotonin as an even more potent blocker of dys-1-associated muscle degeneration than prednisone and serotonin also partially rescued motility [54]. Similarly, serotonin re-uptake blockers, which can cause synaptic serotonin buildup, also significantly reduced degeneration, albeit to a lesser extent that serotonin itself.…”
Section: Translational Neurosciencementioning
confidence: 99%